The Effects of MoO3 Powder Lubrication on Tribological Properties of Sliding Pair Exposed to High Temperature - Yoshinori Takeichi; Marian Dzimko; Uwe Winkelmann (Communications - Scientific letters of the University of Zilina, 2010)
The effect of molybdenum trioxide MoO3 powder on the tribological properties of sliding pair exposed to the temperature up to 700 °C was examined. The experiment showed that MoO3 powder placed directly on the sliding surface of main tribological body influenced and reduced friction values of tested materials. Especially in a temperature range from 500 to 700 °C a clear minimum of friction coefficient around 600 °C was observed. The X-ray diffraction analysis of friction and wear tracks that appeared on specimens showed mixture of different elements which are the product generated during tribological processes at high temperature.